Clinical outcomes of a hydrophobic trifocal diffractive intraocular lens: a literature review - Ristvedt, Deborah; Bosc, Camille; Thompson, Vance (Frontiers in Medicine, 2025)
The aim of this review is to summarize the clinical outcomes reported in patients following the implantation of the hydrophobic diffractive trifocal FineVision HP intraocular lens (IOL). A literature search in PubMed (U.S. National Library of Medicine) was performed to identify publications, both prospective and retrospective, which have reported the clinical outcomes of patients who were implanted with this IOL model after cataract or refractive lens exchange surgeries. A total of 18 clinical studies published between 2019 and 2024 were included in this review. The available data reported in the different clinical publications was analyzed in detail, focusing mainly on refraction, visual acuity, the defocus curve, optical quality, contrast sensitivity, and patient-reported outcome questionnaires. In addition, the adverse events and other measurements reported in some studies were also analyzed. Our review encompassed a total of 1,028 eyes analyzed at different follow-up periods up to a maximum of 24 months. The analysis carried out in this review leads us to conclude that the FineVision HP IOL provides good refractive outcomes and excellent visual performance when implanted.